Investing in our education leading, learning, researching and the doctorate - Rayner, Stephen; Taysum, Alison (Bingley, U.K. : Emerald, 2014)
This volume acknowledges the need for better understanding in leadership, management and administration of new knowledge which is crucial for effective leadership in a period of massive policy reform and deepening austerity in education. The doctorate is key to meeting this global challenge as it offers new and valid ways of enabling innovation and utility in an approach to knowledge creation and management that embodies meaningful methods for assuring improvement, effectiveness, efficiency and equity in education. The chapters in this edited collection emerge from a British Educational Leadership Management and Administration Society (BELMAS) funded Seminar Series. The international leading academics and researching practitioners contributing chapters to the book focus upon purposes, pedagogies and the impact of the doctorate on educational leaders and leadership development. Further, the chapters reveal how doctoral study helps equip leaders to implement policy and develop strategies to steer their organizations towards improving policy provision, and practice.
Introduction : investing in our education? Leading, learning, researching and the doctorate / Alison Taysum, Stephen Rayner -- Academic and professional knowledge in the professional doctorate / David Scott -- Doctoral study in challenging times : entrenching banality or revitalising prospects for 'wicked' intellectual work. The case of Educational Administration / Marlene Morrison -- Leadership : skilled manager or virtuous professional? / Richard Pring -- New directions for the doctoral thesis / Richard Andrews -- Western doctoral programmes as public service, cultural diplomacy or intellectual imperialism? Expatriate educational leadership teaching in the United Arab Emirates / Eugenie A. Samier -- Can we impact leadership practice through teaching democracy and social justice? / Carolyn Shields -- The education doctorate (Ed.D.) and educational leader dispositions and values in England and the United States / Alison Taysum, Charles L. Slater -- Democratic citizenship education and Islamic education : on sceptical doctoral encounters / Yusef Waghid -- Developing nodes in leading networks of knowledge for leader and leadership development : some African students' perspectives on their experience of doctoral education / Emefa Takyi-Amoako -- Investing in our education? Leading, learning, researching and the doctorate / Annette Thomas-Gregory, Justine Mercer -- Conclusions : the doctoral dividend; leading, learning, researching / Stephen Rayner, Alison Taysum.
Includes index.
Print version record
Keywords: Education -- Higher; Education -- Leadership; Higher & further education, tertiary education; Education; Education, Higher; Educational leadership; Education, Higher -- Research; Doctor of philosophy degree